The Stem znh and Prostitution in the Hebrew Bible - Collins, Oral
A Dissertation Presented to the Faculty of the Graduate School of Arts and Sciences. Brandeis University, Department of Near Eastern and Judaic Studies, January 10 1977; University Microfilms 77-13,364; 26-60: prostitution in the Ancient Near East.